Royal Grants and Foreignness between History and Historiography: A Reading about Power and Royal Delegation in the Catholic Monarchy - Ciaramitaro, Fernando (2017)
A thorough reading of Manera de galardón. Merced pecuniaria y extranjería en el siglo XVII, by Victoria Sandoval Parra, allows the debate on some current issues of the monarchy of Spain linked to international historiography: pecuniary royal grants, foreignness and the power of the highest ruler of the empire, the king. Likewise, the book also allows the discussion about the economic-administrative crisis of the Austrian regime and its alternating and dichotomous management of peripheral provinces, between decentralization and centralization.